An Inclusive agri-food systems transformation pathway for India - Singh, Vartika; Das, Prantika; Stevanovic, Miodrag; Jha, Chandan; Bodirsky, Benjamin; Beier, Felicitas; Humpenöder, Florian; Leip, Debbora; Chen, David; Crawford, Michael; von Jeetze, Patrick; Bacca, Edna Molina; et al. (Springer, 2024)
Although India has transformed from a food scarce to a food self-sufficient nation, the challenges of nutrition security, regional inequalities, and unsustainable agricultural practices persist. Existing policies lack an integrated vision for and implementation of holistic food system changes. This study undertakes a food system assessment for India using a global food system modelling framework, evaluating 23 food system measures on 14 indicators across dimensions of health, environment, inclusion, and economy. The food system measures include healthy diets, biosphere protection, agriculture management, equitable livelihood, and external reforms. Results indicate that 13 out of 14 indicators including nutrition and environmental outcomes improve due to synergistic effects driven by coordinated interventions, reducing trade-offs among the four dimensions of the food system. While progress is observed in most health and environmental indicators, challenges such as rising obesity and nitrogen pollution persist. Our attempt to quantify the dynamics of India’s food system under different scenarios enables understanding the trade-offs across dimensions. The comprehensive and forward-looking food system outcomes that this study elucidates aid in the identification of pivotal intervention points and facilitate strategizing policies for transformative changes.